The factors associated with geriatric depression in rural China: stratified by household structure - Gong, Fengfeng; Zhao, Dongdong; Zhao, Yuanyuan; Lu, Shanshan; Qian, Zhenzhong; Sun, Yehuan (Psychology, health & medicine, 2018)
Depressive symptoms and empty nest phenomenon of rural elderly people are both important public health issues, which should not be ignored. We aimed to estimate the prevalence of depressive symptoms and related factors of the empty nest elderly in rural China. We recruited 3182 eligible subjects and gathered data by face-to-face interview. Multivariate logistic regression models were used to explore the related factors of depressive symptoms. The present study showed that the prevalence of depressive symptoms significantly differed between empty nest old adults and non-empty nesters (24.1% vs. 19.0%). The elderly living alone had highest OR of depressive symptoms. Depressive symptoms of empty nest elderly was associated with sleep quality, economic status, pain, social support and ADL. While it was associated with gender, economic status, pain and PSMS in non-empty nest group. Number of chronic disease showed significant associations with depressive symptoms in the elderly living alone. Subjective support, support utilization and pain were positively associated with depressive symptoms in the elderly living with spouse. Sleep quality, economic status and ADL were common factors. Depressive symptoms obviously prevail among empty nest elderly than non-empty nesters. It reminded us that complementary social support from family and society is essential.